Podcasting as a Means of Improving Spanish Speaking Skills in the Foreign Language Classroom: An Action Research Study - Maggie Brennan Juana; Deniz Palak (Networks: An Online Journal for Teacher Research, 2011)
Using action research as a method of inquiry, a high school Spanish teacher undertook this study to understand how podcasting could be used to help improve students’ Spanish speaking skills. Multiple sources of data collected and analyzed by the teacher-researcher in collaboration with her students and other collaborators reveal that the frequency and variety of carefully designed weekly podcasting assignments over time helped improve student speaking skills. This paper provides a framework of reference for other K-12 teachers as to how they could use new technologies successfully and understand the effects in their classrooms.